Application of cloud computing services in e-learning - Lieponienė, Jurgita (Lietuvos matematikos rinkinys, 2013)
According different authors article analyses the importance of cloud computing services in e-learning, examines different cloud computing services types. This article provides an overview of each type of cloud computing services and assesses their application in e-learning.
Keywords: e-learning; e-learning system; cloud computing